Polymer Dispersity Control by Organocatalyzed Living Radical Polymerization - Liu, Xu; Wang, Chen‐Gang; Goto, Atsushi (Angewandte Chemie International Edition, 2019)
Molecular weight distribution of polymers, termed dispersity (Đ), is a fundamental parameter for determining polymer material properties. This paper reports a novel approach for controlling Đ by exploiting a temperature‐selective radical generation in organocatalyzed living radical polymerization. The polymers with tailored Đ were synthesized in a batch system without the assistance of an external pump. A unique aspect of this approach is that Đ was tuneable from 1.11 to 1.50 in any segment in diblock, triblock, and multiblock copolymers and in any form of star and brush polymer without segmental or topological restriction. This approach is amenable to various monomers and free from metals and thus attractive for applications. The approach also generated polymer brushes on surfaces with tailored Đ. An interesting finding was that the polymer brushes exhibited unique interaction with external molecules, depending on the Đ value. Brush up: A novel approach for modulating polymer dispersity was developed. It is based on temperature‐selective organocatalyzed living radical polymerization and enabled dispersity modulation in any segment in linear and branched block copolymers as well as polymer brushes. A dispersity‐dependent size‐exclusion effect to external molecules was observed for the polymer brushes.